Denoising deep brain stimulation pacemaker signals with novel polymer-based nanocomposites: Porous biomaterials for sound absorption - Baraa Chasib Mezher AL Kasar; Shahab Khameneh Asl; Hamed Asgharzadeh; Seyed Jamaleddin Peighambardoust (AIMS Bioengineering)
Deep brain stimulation (DBS) pacemakers are sophisticated medical devices that deliver electrical signals to targeted areas of the brain via implanted electrodes, effectively regulating abnormal brain activity and relieving symptoms of treatment-resistant neurological disorders. However, proximity to other electromagnetic equipment may introduce additional noise, which can be disruptive to individuals. To mitigate this issue, we propose a novel polymer-based nanocomposite for pacemakers for signal denoising. This research focused on the development and analysis of nanocomposites comprising polypropylene (PP) combined with montmorillonite nanoclay and graphene nanosheets (GNs). The nanocomposites were created by blending them through melting, using varying ratios of clay to GNs, with a total loading of 4 wt.%. This study focused on enhancing the signal-to-noise ratio for brain pacemakers by using nanocomposites. It investigated the noise reduction properties of PP nanocomposites, specifically in the outlet gate of the pacemaker. This research aimed to find the ideal ratio of clay to GNs in the PP matrix. X-ray diffraction (XRD) and differential scanning calorimetry (DSC) were conducted to analyze the crystalline structure and filler dispersion, as well as thermal behavior and filler–matrix interactions in the material. Scanning electron microscopy was employed to observe the dispersion of the nanofillers in the PP, and sound tube testing was conducted to evaluate the noise levels of the composites. The findings indicated that a porous structure of the nanocomposite with dispersed microspheres within the PP matrix and a long pathway facilitated increased dissipation of acoustic waves, making it suitable for denoising in brain pacemakers. Furthermore, the nanocomposite containing 2.75 wt.% of nanoclay and 1.25 wt.% of graphene components within the polypropylene matrix demonstrated a favorable signal-to-noise ratio compared to other evaluated nanocomposites.